The Neutrophil-to-lymphocyte ratio as a diagnostic and prognostic biomarker in pulmonary hypertension: A systematic review - Khanzadeh, Shokoufeh; Aminizadeh, Sarina; Nourigheimasi, Shima; Lucke-Wold, Brandon; Rashidi, Farid; Kaymaz, Cihangir; Janda, Pavel; Reis, Abilio; Goutnik, Michael; Khanzadeh, Monireh; Bazrafshan Drissi, Hamed; Chichagi, Fatemeh (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background: The objective of this systematic review is to provide an overview of research that examined the relationship between pulmonary hypertension (PH) and the neutrophil-to-lymphocyte ratio (NLR).Methods: To identify the studies related to NLR, a search was done on PubMed, Scopus, and Web of Science with an end date of  March 30th, 2023. A total of 25 studies were included in the review. These studies included a variety of pathologies that contribute to PH. We employed the Newcastle-Ottawa Scale to assess the quality of studies. For all studies, a significance level of P˂0.05 was used.Results: In patients with sarcoidosis, chronic obstructive pulmonary disease, systemic sclerosis, chronic kidney disease, and congenital heart disease, NLR appears to be an independent predictor of PH. Also, it was frequently linked to the result, complications, and severity of the disease in PH patients.Conclusion: NLR may be utilized as a repeatable, inexpensive, and trustworthy proxy for the onset and severity of PH.